Aortic dissection-induced acute flaccid paraplegia treated with cerebrospinal fluid drainage - Eduardo Leal Adam; Henrique Lane Staniak; Rodolfo Sharovsky; Adriano Ferreira da Silva; Cláudio Campi de Castro; Márcio Sommer Bittencourt (University of São Paulo, 2012)
Acute aortic dissection is a life-threatening event in which prompt and correct diagnosis is associated with better outcomes. In most cases, there is chest or back pain. However, in rare cases, patients have little or no pain and other symptoms are more conspicuous at presentation. The autors reports the case of a 47-year-old female patient who sought medical attention for sudden-onset paraplegia. The physical examination was normal except for bilateral lower limb flaccid paralysis, with abolition of deep tendon reflexes and paraesthesia in both feet. Computed tomography showed aortic dissection, with partial thrombosis of the false lumen, starting after the emergence of the left subclavian artery and extending, toward the bifurcation of the aorta, to the left iliac artery. After cerebrospinal fluid drainage, the evolution was favorable.